Earnings Dynamics and Inequality among Canadian Men, 1976–1992: Evidence from Longitudinal Income Tax Records - Baker, Michael; Solon, Gary (Journal of Labor Economics, 2003)
Using an extraordinary database drawn from longitudinal income tax records, we decompose Canada’s growth in earnings inequality into its persistent and transitory components. We find that the growth in earnings inequality reflects both an increase in long‐run inequality and an increase in earnings instability. The Canadian data strongly reject several restrictions commonly imposed in the U.S. literature, and they also suggest that imposing these evidently false restrictions may lead to distorted inferences about earnings dynamics and inequality trends.